ANALYSIS OF THE COMPLIANCE OF IMPLEMENTING PERFORMANCE ALLOWANCES FOR CIVIL SERVANTS AT LEMDIKLAT POLRI WITH THE PROVISIONS OF THE INDONESIAN NATIONAL POLICE CHIEF REGULATION NUMBER 7 OF 2020 - Supriyadi, Rita Sahara; Giyanto, Bambang; Asropi, Asropi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The research evaluates the implementation of performance allowance policies for Civil Servants at Lemdiklat Polri (Indonesian National Police Education and Training Institute). The bureaucratic structure effectively supports policy implementation due to Standard Operating Procedures (SOP) from the central authority serving as a reference. However, inter-organizational communication faces obstacles when interacting with employees as the target group. Information about National Police Chief Regulation Number 7 of 2022 and Employee Performance Appraisal (SKP) procedures has not been adequately communicated, leading to discrepancies in performance allowances and SKPs.Insufficient human resources can impact the policy's success, especially in Lemdiklat Polri's Human Resources Department (Bag SDM Rorenmin). However, infrastructure and facilities seem adequate to support policy implementation. Policy implementers still lack a high commitment to their duties as per National Police Chief Regulation Number 7 of 2020. Delays in monthly performance allowance disbursement are common due to tardiness in attendance summaries and processing requests. This reflects that policy commands aren't fully executed by the target group, primarily due to ineffective communication influencing their behaviour. Addressing these challenges is essential to implement performance allowance policies at Lemdiklat Polri successfully.Keywords: Compliance, Performance Allowances and National Police Chief Regulation Number 7 of 2020